Induction of settlement and metamorphosis in the tropical oyster, crassostea belcher/ (sowerby), by neuroactive compounds. - Shau , Hwai Tan (Universiti Sains Malaysia, 1995)
Larvae of the tropical oyster Crassostrea belcheri set and metamorphosed when exposed to epinephrine (EPI), norepinephrine (NE), L-3,4-dihydroxyphenylalanine (L-DOPA) and gamma-amino butyric acid (GABA). The optimum concentration of these neuroactive compounds was 10-5 M when larval set increased from 20% in the controls to between 60-80%. Larval setting performances were generally depressed when exposure was extended to 24 hours compared to 1 hour.